Mesenchymal stem cells control alloreactive CD8+CD28− T cells. (24th October 2013) - Engela, A. U.; Baan, C. C.; Litjens, N. H. R.; Franquesa, M.; Betjes, M. G. H.; Weimar, W.; Hoogduijn, M. J.
Summary: CD28/B7 co‐stimulation blockade with belatacept prevents alloreactivity in kidney transplant patients. However, cells lacking CD28 are not susceptible to belatacept treatment. As CD8 + CD28 − T‐cells have cytotoxic and pathogenic properties, we investigated whether mesenchymal stem cells (MSC) are effective in controlling these cells. In mixed lymphocyte reactions (MLR), MSC and belatacept inhibited peripheral blood mononuclear cell (PBMC) proliferation in a dose‐dependent manner. MSC at MSC/effector cell ratios of 1:160 and 1:2·5 reduced proliferation by 38·8 and 92·2%, respectively. Belatacept concentrations of 0·1 μg/ml and 10 μg/ml suppressed proliferation by 20·7 and 80·6%, respectively. Both treatments in combination did not inhibit each other's function. Allostimulated CD8 + CD28 − T cells were able to proliferate and expressed the cytolytic and cytotoxic effector molecules granzyme B, interferon (IFN)‐γ and tumour necrosis factor (TNF)‐α. While belatacept did not affect the proliferation of CD8 + CD28 − T cells, MSC reduced the percentage of CD28 − T cells in the proliferating CD8 + T cell fraction by 45·9% ( P  = 0·009). CD8 + CD28 − T cells as effector cells in MLR in the presence of CD4 + T cell help gained CD28 expression, an effect independent of MSC. In contrast, allostimulated CD28 + T cells did not lose CD28 expression in MLR–MSC co‐culture, suggesting that MSC control pre‐existing CD28 − T cells and not newly induced CD28 − T cells. In conclusion, alloreactive CD8 + CD28 − T cells that remain unaffected by belatacept treatment are inhibited by MSC. This study indicates the potential of an MSC–belatacept combination therapy to control alloreactivity.